Inhibitors: Diagnostic challenges, unknowns of inhibitor development, treatment of bleeding and surgery, and insights into diagnosis and treatment in China. (6th May 2022) - Escuriola Ettingshausen, Carmen; Yang, Renchi; Wu, Wenman; Meeks, Shannon L.
Abstract: Factor (F) VIII inhibitors develop in around 30% of previously untreated patients (PUPs) with severe haemophilia, to a lesser extend in moderate and mild haemophilia A and in up to 10% in severe haemophilia B. Diagnostic challenges and questions remain including access to high quality testing, the role for functional inhibitor testing and binding antibody testing, and the adaptations needed in the presence of non‐factor replacement therapy. Despite significant gains in knowledge there are still many unanswered questions underlying the immunologic mechanisms of inhibitor development and tolerance. Therapeutic options include eradication of inhibitors using immune tolerance induction therapy (ITI), prophylaxis with bypassing agents (i.e., recombinant activated factor VII /rFVIIa or activated prothrombin complex concentrate/aPCC) or non‐factor replacement therapies (e.g., emicizumab) and treatment of bleeds or coverage of surgeries/invasive procedure. Recently a haemophilia centre capacity building program was launched in China to further develop the infrastructure and support needed to improve the diagnosis of haemophilia, detection of inhibitors, and continue to improve the care of patients with haemophilia and inhibitors. Abstract :